44. ROLE OF BIPOLAR IN HIP ARTHROPLASTY (Vietnam Journal of Community Medicine, 2024)
Objective: Present some complications of bipolar warning the disadvantages of this arthroplasty.Method: Descriptive  retrospective one - case report.Case presentation: two - time postoperative dislocations of bipolar arthroplasty. Successful closed reductions, but coxitis  after  2-year follow-up.Result: Bipolar hip arthroplasty was presented, with complications of dislocations. Despite successful closed reduction but developing coxitis make bipolar less functional than total hip arthroplasty. These unsatisfied results  warn  the surgeon ahead bipolar indication.Conclusion: In expection of replacement for total hip arthroplasty. But clinical reality shows that bipolar presumes replace the Moore prosthesis.
Keywords: Bipolar hip arthroplasty; coxitis; postoperative dislocation